1994
DOI: 10.1093/rheumatology/33.5.442
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Early Somantic, Radiological, Congnitive and Psychosocial Findings and Outcome During a One-Year Follow-Up in 117 Patients Suffering From Common Whiplash

Abstract: SUMMARYTo analyse the significance of the interplay between somatic and psychosocial factors in influencing the course of recovery a non-selected well defined group of 117 whiplash patients was investigated. Initial examination was performed, on average, 7.2 ± 4.2 days after trauma and follow-ups were carried out at 3, 6 and 12 months. At the initial investigation all patients were given a neurological examination, cognitive and psychosocial factor assessment and cervical spine X-rays. At each follow-up stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 35 publications
0
58
1
4
Order By: Relevance
“…Significant factors in this regard include previous whiplash injury, previous neck symptoms or headache, previous psychological problems, occurrence of acute eye symptoms, multiple symptoms, female gender and older age, work disability limited selfconfidence and limited education [13,14,28,39,53,88,90,118,127,142,173,185,187,195,209,212,[248][249][250]257]. The importance of various vehicle-and impact-related factors has also been studied [61,94,113,114,132,133,141,260] Studies of the roles of all these prognostic factors in the development of long-term symptoms in whiplash patients have produced inconsistent results, since several of the factors considered in the above, as well as in other studies and reviews, have not been found to be related to unfavourable prognosis.…”
Section: Other Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant factors in this regard include previous whiplash injury, previous neck symptoms or headache, previous psychological problems, occurrence of acute eye symptoms, multiple symptoms, female gender and older age, work disability limited selfconfidence and limited education [13,14,28,39,53,88,90,118,127,142,173,185,187,195,209,212,[248][249][250]257]. The importance of various vehicle-and impact-related factors has also been studied [61,94,113,114,132,133,141,260] Studies of the roles of all these prognostic factors in the development of long-term symptoms in whiplash patients have produced inconsistent results, since several of the factors considered in the above, as well as in other studies and reviews, have not been found to be related to unfavourable prognosis.…”
Section: Other Prognostic Factorsmentioning
confidence: 99%
“…Approximately 70% of the injured recover within a few days up to 2-3 weeks. ; approximately 20% of the injured have remaining symptoms, but these do not impair their working ability, while approximately 5-10% experience limitations in their work and leisure activities [212,242,250]. If symptoms persist more than 2 months after a whiplash injury, there is a considerable risk of long-term problems [159].…”
Section: Prognostic Factors For Long-term Symptomsmentioning
confidence: 99%
“…27 In addition, a positive correlation has been established between severity of injury and delayed recovery. [28][29][30] Neck complaint of pain, stiffness or tenderness and fracture or dislocation…”
Section: Chronic Whiplash Syndromementioning
confidence: 99%
“…35 Chronic cases have an increased risk of developing other longterm health complaints, such as headaches, fatigue, sleep disturbance, thoracic pain, low back pain and general ill health. 36 Depression and anxiety 37,38 and lower performance in concentration and attention tests 28,39 may also be observed, although causality in these cases remains controversial. 40 These findings support the notion that psychological overlay may play an important role on general physical well-being and the development of CWS.…”
Section: The Impact Of Psychological Overlay On Recoverymentioning
confidence: 99%
“…Multiple studies have documented that neck pain and headaches can persist in significant numbers of patients.A well-designed prospective study reported the following percentages of patients with complaints of neck pain and headaches, respectively, at various times after the injury: 92% and 57% -1 week, 38% and 35% -3 months, 25% and 26% -6 months, 19% and 21% -1 year, and 16% and 15% -2 years [62,63]. Symptoms present two years after injury are still present ten years after the injury [27].…”
Section: Prognosis and Complicationsmentioning
confidence: 99%